PENERAPAN MODEL PEMBELAJARAN TIME TOKEN DISERTAI MEDIA KARTU SOAL TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMAN 1 RUPAT UTARA - Vimala Valentina; Syahril Syahril; M. Nor M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to describe the learning outcomes of Senior High School 1 rupat utara students by applying the time token learning model accompanied by question card media and knowing the difference in learning outcomes between students who apply the time token learning model accompanied by the question card media with conventional models. The research method used was a quasi-experimental design with posttest-only design. The population is all students of class XI Science Senior High School 1 Rupat Utara in the 2018/2019 school year. The sample consisted of two classes, namely class XI Science 1, which numbered 30 people as the experimental class and class XI Science 2, which numbered 29 people as the control class. This research instrument uses cognitive test questions. Data were analyzed descriptively by looking at differences in students cognitive learning outcomes between the experimental class and the control class then analyzed inferentially using the T-Test. The results of data analysis obtained are the average absorption of the experimental class with the value obtained is 79.17% and 72.07% control class. The absorption percentage of the experimental class and the control class are in the good category with a value difference of 7.1%. Based on the results of this research it can be concluded that the application of the time token learning model along with the media card questions can improve student cognitive learning outcomes in the material temperature, heat, and heat transfer of class XI Science in Senior High School 1 Rupat Utara.Key Words: Time Token, Question card, Cognitive Learning Outcomes